Acanthomatous ameloblastoma of the mandible: a recurrent odontogenic tumor mimicking multiple cystic lesions: a case report - Chandrama; Dahiya, Manisha; Agrawal, Namrata (International Journal of Basic & Clinical Pharmacology, 2026)
Ameloblastoma is a benign but locally aggressive odontogenic tumor characterized by a high recurrence rate. Among its histopathological variants, acanthomatous ameloblastoma is uncommon and often poses a diagnostic challenge due to its resemblance to other cystic and neoplastic jaw lesions. We reported a case of recurrent acanthomatous ameloblastoma involving the left posterior mandible in a young adult male with a prior surgical history. The lesion presented as a slowly progressive swelling associated with tooth mobility and pus discharge. Clinical, radiographic, surgical, and histopathological findings were correlated to arrive at a definitive diagnosis. This case highlights the importance of comprehensive evaluation and long-term follow-up in managing recurrent ameloblastomas.